Gonadotropin‐releasing hormone agonists for ovarian protection during cancer chemotherapy: systematic review and meta‐analysis. (1st December 2017) - Senra, J. C.; Roque, M.; Talim, M. C. T.; Reis, F. M.; Tavares, R. L. C.
ABSTRACT: Objective: To evaluate the effectiveness of gonadotropin‐releasing hormone agonist (GnRHa) administration before and/or during cancer chemotherapy for the protection of ovarian reserve in premenopausal women without prior diagnosis of infertility. Methods: This was a systematic review and meta‐analysis of randomized controlled trials (RCTs) comparing administration of GnRHa before and/or during chemotherapy vs chemotherapy alone. Eligible participants were premenopausal women at any stage of cancer, without previous diagnosis of infertility. An electronic database search in MEDLINE, CENTRAL, LILACS andClinicalTrials.gov was performed. After selecting eligible studies, the relative risk (RR) was assessed for primary ovarian insufficiency (POI)/amenorrhea and for spontaneous pregnancy after completion of treatment. Results: Thirteen RCTs comparing concurrent use of GnRHa and chemotherapy (609 participants) with chemotherapy alone (599 participants) were eligible for meta‐analysis. All trials were open‐label and patients had been treated for breast cancer ( n  = 1099) or lymphoma ( n  = 109). GnRHa had a significant benefit on the risk of POI/amenorrhea (RR, 0.60; 95% CI, 0.45–0.79), which persisted in subgroup analysis for breast cancer (RR, 0.57; 95% CI, 0.43–0.77) but not for lymphoma patients (RR, 0.70; 95% CI, 0.20–2.47). The rate of spontaneous pregnancy after completion of treatment was higher in women receiving GnRHa plus chemotherapy compared with those receiving chemotherapy alone (RR, 1.43; 95% CI, 1.01–2.02). Overall, the quality of evidence was low due to the unclear risk of bias, short follow‐up and lack of objective assessment of ovarian function and reserve. Conclusions: Evidence, albeit of low quality, supports the use of GnRHa before and/or during chemotherapy to reduce the risk of POI and increase the probability of spontaneous pregnancy in the short term. Further high quality RCTs with more accurate assessment of ovarian reserve are needed to support definitive recommendations for clinical practice. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.